La reestructuración de la Armada Argentina entre el final del siglo XX y principios del XXI - Soprano, Germán (Antíteses.)
The definition of a policy of national defense and internal security in democracy, created conditions to advance in the process of restructuring of the Argentina Navy, introducing changes in its organization and functions. In this article we will focus this process analyzing, on the one hand, the relationship between the definitions of defense policy and the configuration of naval military instrument between the end of the twentieth century and early twenty-first century; and, on the other hand, understanding their development in the case of two components of the force: the marine corps and the division of maritime patrol.